Comparative Analysis of Public Economic Domains: A Weighted Product Method Approach - Manjula Selvam (REST Journal on Data Analytics and Artificial Intelligence, 2026)
This study employs the Weighted Product Method (WPM) to comprehensively evaluate and compare five critical domains of public economics: Development Economics, Political Economy, Environmental Economics, Health Economics, and Labour Economics. Health Economics, and Labour Economics. The fields are assessed using four key criteria: relevance, effectiveness in addressing market failures, criticism and limitations, and influence on inequality. The results indicate notable differences among the economic domains, with Labour Economics ranking first with a preference score of 0.87978 due to its strong ability to address market failures and generate economic impact. Environmental Economics ranks second, reflecting its high relevance and effectiveness despite facing critical challenges. Development Economics and Political Economy demonstrate moderate performance, while Health Economics indicates scope for methodological enhancement. Equal weighting was adopted to maintain fairness and objectivity in the assessment. the WPM framework provides a comprehensive comparative evaluation, highlighting the strengths and limitations of different economic fields and supporting future research, policy formulation, and interdisciplinary economic decision-making.